Case for diagnosis. Suppurative nodule or something deeper? - Nuno Preto Gomes; Miguel Costa-Silva; Elisabete Moreira; Filomena Azevedo (Sociedade Brasileira de Dermatologia, 2019)
Abstract: The authors report the case of a 62-year-old man with a history of total left hip arthroplasty nine years previously presenting with a large infiltrated plaque on the posterior area of the left thigh with three months of evolution without systemic symptoms or elevated inflammatory markers. Computed tomography of the left lower limb revealed a 12-centimeter linear extension of the lesion to the posterior part of the left proximal femur. Prosthesis joint infection, although rare, is a surgical complication to be taken into account, even if the surgery was performed many years before.